شیكردنەوەی ناوەڕۆكی كتێبی بیركاری قۆناغی (6 - 8) ی بنەرەتی لە هەرێمی كوردستان بەپێی پێوەری (NCTM) - محمد, سۆلاڤ فائق; محمد, ئاریان علی; حسن, چۆپی رووف (Sulaimani Journal for Humanities)
For the sake of its educational goals in all its different dimensions and for mathematic subject, a perfect program has been prepared, also for detecting the strengths and weaknesses of the mathematics program, answering this question shows What is the availability of (NCTM) in the content of mathematics textbooks for primary school grades (6-7-8) The researcher used (NCTM) criteria as a research tool for the fields of (numbers and operations, algebra, geometry, measurement) in order to achieve the goal of the research, which is to analyze the content of mathematics textbooks for primary School grades (6-8) n Kurdistan Region according to (NCTM) measurement, after ensuring the accuracy and stability of the measure, the researcher analyzed the mathematics textbooks of primary grades (6-8). The research method is (analytical description) and the scope of the research is the content of mathematics text books (6 seventh edition in 2016, grade 7 tenth edition in 2018 and grade 8 eleventh edition in 2019). The research sample includes all the common topics between the books of all three stages. After conducting the analysis, the researcher reached the following conclusions: The availability of the scale for numbers, operations and algebra is weak for primary grades)6-8(. The availability of the scale for geometry is intermediate for grade six, good for grade seven and grade eight textbook. The availability of the scale for the measurement field is intermediate for grade six textbooks, weak for grade seven and grade eighth textbooks